PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI SALAH SATU HOTEL DI BANDUNG - Fauzany, Riffka; Hatimatunnisani, Hani; Nurfadilah, Haifa; Hadi, Samsul (Jurnal Perhotelan dan Pariwisata, 2022)
There are several factors that can affect employee work productivity, including compensation and work environment. This study aims to determine the effect of compensation and work environment on employee work productivity at a Hotel in Bandung. This study used a quantitative method with a sample of 61 employees. The results showed that compensation and work environment had a positive and significant effect on work productivity by 82.5% while the remaining 17,5% was explained by other factors. The existence of good compensation and a supportive work environment can increase employee productivity at work.